Historicizing Sunni Islam in the Ottoman Empire, c. 1450-c. 1750 - Krstić, Tijana; Terzioğlu, Derin, 1969- (Islamic history and civilization. studies and texts, 2020)
"Articles collected in Historicizing Sunni Islam in the Ottoman Empire, c. 1450-c. 1750 engage with the idea that "Sunnism" itself has a history and trace how particular Islamic genres-ranging from prayer manuals, heresiographies, creeds, hadith and fatwa collections, legal and theological treatises, and historiography to mosques and Sufi convents-developed and were reinterpreted in the Ottoman Empire between c. 1450 and c. 1750. The volume epitomizes the growing scholarly interest in historicizing Islamic discourses and practices of the post-classical era, which has heretofore been styled as a period of decline, reflecting critically on the concepts of 'tradition', 'orthodoxy' and 'orthopraxy' as they were conceived and debated in the context of building and maintaining the longest-lasting Muslim-ruled empire. Contributors: Helen Pfeifer; Nabil al-Tikriti; Derin Terzioğlu; Tijana Krstić; Nir Shafir; Guy Burak; Çiğdem Kafesçioğlu; Grigor Boykov; H. Evren Sünnetçioğlu; Ünver Rüstem; Ayşe Baltacıoğlu-Brammer; Vefa Erginbaş; Selim Güngörürler"--